2020
DOI: 10.1016/j.csbj.2020.06.039
|View full text |Cite
|
Sign up to set email alerts
|

Rich-club in the brain’s macrostructure: Insights from graph theoretical analysis

Abstract: The brain is a complex network. Growing evidence supports the critical roles of a set of brain regions within the brain network, known as the brain’s cores or hubs. These regions require high energy cost but possess highly efficient neural information transfer in the brain’s network and are termed the rich-club. The rich-club of the brain network is essential as it directly regulates functional integration across multiple segregated regions and helps to optimize cognitive processes. Here, we review the recent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 143 publications
1
36
0
Order By: Relevance
“…Especially vulnerable (but not exclusive to scale-free networks) is the rich club (Zhou and Mondragón, 2004 ), a group of hubs with a high degree of interconnectivity between each other. While there is growing evidence for the presence of rich-club topology in the brain (Griffa and Van den Heuvel, 2018 ; Kim and Min, 2020 ) the presence of scale-free topology (Bonifazi et al, 2009 ) is still somewhat controversial, but it provides important insight in modeling studies of dynamics on network topology (Broido and Clauset, 2019 ).…”
Section: Criticality and Networkmentioning
confidence: 99%
“…Especially vulnerable (but not exclusive to scale-free networks) is the rich club (Zhou and Mondragón, 2004 ), a group of hubs with a high degree of interconnectivity between each other. While there is growing evidence for the presence of rich-club topology in the brain (Griffa and Van den Heuvel, 2018 ; Kim and Min, 2020 ) the presence of scale-free topology (Bonifazi et al, 2009 ) is still somewhat controversial, but it provides important insight in modeling studies of dynamics on network topology (Broido and Clauset, 2019 ).…”
Section: Criticality and Networkmentioning
confidence: 99%
“…One of the most well-known neural topographic structures has been described as being a rich club , characterized by clusters in which every node is connected with every other node in that cluster. Recently, Kim and Min (2020) take a graph theoretical approach to describing the rich-club structure in the brain [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The rich-club of the brain network plays a critical role in global integration of neural information and is essential for efficient communication across multiple segregated and distant brain regions. 26,27 Therefore, network disruptions within the rich club have a direct impact on various behavioral and cognitive tasks. Connectivity-based neuroimaging studies have identified alterations in rich-club network in several neuropsychiatric disorders.…”
Section: Discussionmentioning
confidence: 99%